Quality of life in patients on chronic dialysis in South Africa: a comparative mixed methods study. Issue 1 (December 2017) - Tannor, Elliot; Archer, Elize; Kapembwa, Kenneth; van Schalkwyk, Susan; Davids, M.
Abstract Background The increasing prevalence of treated end-stage renal disease and low transplant rates in Africa leads to longer durations on dialysis. Dialysis should not only be aimed at prolonging lives but also improve quality of life (QOL). Using mixed methods, we investigated the QOL of patients on chronic haemodialysis (HD) and peritoneal dialysis (PD). Methods We conducted a cross-sectional study at Tygerberg Hospital in Cape Town, South Africa. All the PD patients were being treated with continuous ambulatory peritoneal dialysis. The KDQOL-SF 1.3 questionnaire was used for the quantitative phase of the study. Thereafter, focus-group interviews were conducted by an experienced facilitator in groups of HD and PD patients. Electronic recordings were transcribed verbatim and analysed manually to identify emerging themes. Results A total of 106 patients completed questionnaires and 36 of them participated in the focus group interviews. There was no difference between PD and HD patients in the overall KDQOL-SF scores. PD patients scored lower with regard to symptoms (P  = 0.005), energy/fatigue (P  = 0.025) and sleep (P  = 0.023) but scored higher for work status (P  = 0.005) and dialysis staff encouragement (P  = 0.019) than those on HD. Symptoms and complications were verbalised more in the PD patients, with fear of peritonitis keeping some housebound. PD patients were more limited by their treatment modality which impacted on body image, sexual function and social interaction but there were less dietary and occupational limitations. Patients on each modality acknowledged the support received from family and dialysis staff but highlighted the lack of support from government. PD patients had little opportunity for interaction with one another and therefore enjoyed less support from fellow patients. Conclusions PD patients experienced a heavier symptom burden and greater limitations related to their dialysis modality, especially with regards to social functioning. The mixed-methods approach helped to identify several issues affecting quality of life which are amenable to intervention.